Inheritance of Plant and Ear Height in Maize (Zea Mays L.) - Zsubori, Zsuzsanna; Gyenes-Hegyi, Zsuzsanna; Illés, Ottó; Pók, István; Rácz, Ferenc; Szőke, Csaba (Acta Agraria Debreceniensis, 2002)
Plant and ear height are very important characters not only for describing new varieties of maize (Zea mays L.), but for green and dry matter production, and even for grain yield. Significant positive correlations have been reported by various authors between plant height and stover yield, plant height and dry matter yield, and plant height and grain yield. The height of the main ear is also correlated to plant height. It depends on the variety or the environment, but is likely to be the same height within a population. Many environmental and agronomical factors (e.g. plant density, fertilization, pests and diseases) influence the expression of these characters, which are not quality traits. Their expression is controlled by many genes and by the interactions between these genes. The heritability of these traits is high and they show significant genotypic variability and positive heterosis, as reported in many research publications.